Os meios jurisdicionais de soluções de controversias internacionais: características e diferenças / Judicial Instruments for the Settlement of International Disputes: characteristics and differences - Lima, Mario Jorge P. de C. (Revista do Programa de Pós-Graduação em Direito, 2015)
The settlement of disputes between independent human communities has always developed preferably throughout history by peaceful means of settlement, which reveal themselves as more rational means and consistent for progress. The means of peaceful agreement are classified as diplomatic, political and judicial settlement. Disputes in international law are solved by any of these agreement species, because there is no unified international justice ordination, and among them, the media called judicial settlement, which are the arbitration and permanent courts, realize more fully the judicial function, especially the last, in remarkable development since the middle of last century. In this paper, we intend to extend the analysis of the characteristics and differences between these two types of international judicial setllements.